Areas of economic cooperation of Ukraine аnd Middle East сountries - Анкаві, Саєд С. М. (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
This article studies economic cooperation development of Ukraine and the countries of the Middle East, defines major factors of modern international integration process which influences the formation of the external economic strategy of the states of the region. The article researches the bilateral trade of the Middle East countries, the development of foreign economic relations between Ukraine and the countries of the Middle East. The directions of pre-conditions of the international economic cooperation development are defined, practical recommendations on the realization of trade and investment forms of the cooperation between Ukraine and the countries of the Middle East under the modern conditions are given.